On the use of information technologies in the process of physical education of student youth - Shankovsky, Andriy; Vypasniak, Igor (Journal of Education, Health and Sport, 2017)
Topicality. The determining of the level of effectiveness of using information technology in shaping the informational educational environment of students’ physical education in the system of education and beyond, the identification of the general theoretical basis of study, necessary for didactic development of approaches of the use of information technology in the physical education of students, requires the organization of a special research. Objectives of the study: to analyze and systematize modern scientific and methodological knowledge and the results of practical experience of domestic and foreign researchers in the sphere of the use of information technologies in the practice of physical education of students; to develop informational and methodical multimedia system “Рerfectum corpus”, as a means of raising the level of theoretical knowledge of students in the process of physical education. Research results. The results of the qualifying experiment led us to develop the multimedia information and methodical system “Рerfectum corpus” as an auxiliary means of training for the use in class and in the extracurricular format, which is intended for self-study and raising the level of theoretical knowledge, motivation of students for physical exercises. Each module of the multimedia information and methodical system “Рerfectum corpus” consists of sections that may contain background images, buttons and other options of visual representation. Conclusions. The analysis of scientific sources testifies that the use of information technologies in the practice of physical education of student youth opens new opportunities for increasing the efficiency of the process of physical education. The developed information-methodical system includes three modules: “Useful to know”, “Practice”, “Bonus".